Development of Camp Motivation Scale and Determination of Camper Profiles - YASAR, Birol Çagatay; ARDAHAN, Faik (International Journal of Holistic Health, Sports and Recreation, 2024)
The purpose of this study is to develop the “Camping Motivation Scale - CMS” to determine the factors that motivate individuals to go camping and to determine camper profiles. Within the scope of the study, which is a descriptive research, total 386 data were collected from adult individuals who camped for recreational purposes in camping areas using the decisional sampling method and face-to-face survey method. The survey form consists of a 56-item list of questions that examine the purpose of individuals camping, in addition to information about demographics. In the study, the Kaiser-Mayer-Olkin value was found to be 0.930 and the values ​​of the Bartlett sphericity tests were found to be x²=14693.400 SD=990, p=0.000. According to the results, Explanatory Factor Analysis was applied to the scale. The Cronbach’s Alpha coefficient of the CMS was found to be 0.955 and the variance it explained was 67.1%. CMS; “Physical/Mental Health and Desireto Rest”, “Attractiveness of Place and Servise Quality”, “Seeking Innovation/Development”, “Recognition and Social Status”, “Getting Away From”, “Fun”, “Nostalgia”, “Setting an Example”, “Socialization” and “Desire to Visit and Participate in Activities” are factored in10 factors. Confirmatory Factor Analysis was applied to the scale and when the fit indices were examined, it was seen that the ratio of the chi-square value to the degree of freedom (3588.00 / 1439 = 2.49) had a "Perfect Fit" value. When other fit indices were examined, RMSEA = 0.062 "Good Fit", NFI = 0.95 "Perfect Fit", CFI = 0.97 "Perfect Fit", GFI = 0.75 "Moderate Fit" was seen. The results show that the CMS is valid and reliable for the Turkish population. In addition, when cluster analysis was applied to the scale, according to CMS, three different camper profiles have emerged as "Conscious", "Standard" and "Unconscious".